Are genotoxic and carcinogenic compounds present in Malaysian traditional medicines and herbal supplements? a review based on the Malaysian herbal monograph - M. Pauzi, Nur Azra; Cheema, Manraj Singh; Ismail, Amin; Ghazali, Ahmad Rohi; Abdullah, Rozaini (Universiti Putra Malaysia, 2021)
The use of medicinal plants is significant in the long tradition of folklore and traditional medicine in Malaysia, which continues to the present day. To support the growth of the local herbal industry, the Malaysian Herbal Monograph (MHM) was introduced, with monographs of 76 commonly used local medicinal plants published to date. Despite their health benefits and important pharmacological activities, 11 plant species that could potentially contain genotoxic and carcinogenic phytochemicals such as alkenylbenzenes (methyleugenol, safrole and estragole) and pyrrolizidine alkaloids (monocrotaline, lasiocarpine, riddelliine and senecionine) were investigated. A further search on QUEST3+, a database maintained by the National Pharmaceutical Regulatory Agency, Ministry of Health Malaysia, revealed that hundreds of registered natural products, including traditional medicines and herbal supplements (TMHS), contain these plant species as ingredients. In conclusion, consumers could be exposed to genotoxic and carcinogenic phytochemicals through consumption of these registered TMHS thus increasing the risk of developing cancer.